Red Hat Linux Bible: Fedora and Enterprise Edition - Negus, Christopher (John Wiley & Sons, 2011)
Use this comprehensive guide to harness the power of Red Hat Linux on a server, desktop, or laptop computer. Coverage includes desktop and server basics, simple, painless installations, Linux Shell, using VmWare, VNC, and more.